Nationwide Express / Mohamad Hanif Rahman … [et al.] - Rahman, Mohamad Hanif; Misran, Mohd Helmi; Barjumin, Zari Muhamad Hafiez; Abd Rahman, Mohd Redzuan; Majnis, Mohd Faizal (2000)
Nationwide express is an express delivery service, five friends core out an idea to established this company in year 2005 with paid up capital RM 52,096.00. with their partner consist of Mohd Hanif B. Rahman, Redzuan B. Abdul Rahman, Zari Muhamad Hafiez B. Barjumin, Mohd Helmi B. Misran and Mohd Faizal B. Majnis. This is a 100% bumiputra owned company address at No. 35 Jin PPM 8, Plaza Pandan Malim, 75250, Malacca Realizing the growth of businesses and large company in the new millennium we found many existing opportunities to set up and express delivering and postal services. Thus, we took this opportunity to fulfill this needs. Realizing the importance of fast and save delivery we establish this services covering every district in Melaka including Alor Gajah, Melaka Tengah, Jasin and every state in peninsular Malaysia. The services charge is affordable based on the distance and the weight of the good delivered. Every delivery is guaranteed to be send the day after. Because we are using Nationwide Express as our company name, we won’t be facing many problems to get to our customer because Nationwide Express is already a well-known company, we also used “fast and save” as our motto to attract more customers.